Isolation and cloning of the promoter sequence of Vitamin E Biosynthesis gene (Homogentisate phytyltransferase) from oil palm - Yamba, Mohd Saiful (2016)
The oil palm tissue contains vitamin E in the form of tocotrienols and tocopherols. The combination of prenyldiphosphate and homogentisic acid (HGA) is the first committed step in vitamin E production. The reaction is catalyzed by homogentisate phytyltransferase (HPT). The oil palm genomic sequence containing the HPT gene is used to study the expression of HPT gene in oil palm tissues. The objective of this study is to isolate and clone the HPT promoter sequence. To obtain the result from this study, some molecular work was done, including DNA extraction by DNA extraction kit and the cetyltrimethylammonium bromide (CTAB) method, designing the primer for HPT promoter isolation, running the polymerase chain reaction (PCR) to get the HPT promoter sequence and performing agarose gel purification to purify the HPT promoter sequences. After obtaining the amplified HPT promoter sequence, the HPT promoter was introduced into an entry vector and then to destination vector forming the expression clone.